(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
The Reivers (1962) is a humorous Southern novel by William Faulkner (1897–1962) that follows eleven-year-old protagonist Lucius Priest on a journey to Memphis, involving a stolen car and misadventures with crime, race, and morality in the early 20th-century American South. This study aims to explore how the protagonist’s journey from boyhood to manhood reflects the tensions between traditional and evolving notions of masculinity in contemporary society. Employing Michael Kimmel’s concept of ‘The Guy Code,’ the study investigates how the adolescent male protagonist navigates and internalizes societal expectations of manhood in the novel. Faulkner’s depiction of boyhood to manhood transitions serves as a vivid narrative to analyze themes of honor, loyalty, rites of passage, and the consequences of deviating from traditional norms within the sociocultural landscape of early 20th-century Southern America. Through textual analysis and thematic exploration, this research seeks to uncover the complexities of male identity formation, showing how the narrative questions or reinforces the prevailing cultural constructs of masculinity. By examining the interactions, behaviors, and emotional landscapes of the characters, this study contributes to a comprehensive understanding of gender roles and the dynamics of masculinity as portrayed in literary discourse and society.